Off‐target inhibition of NGLY1 by the polycaspase inhibitor Z‐VAD‐fmk induces cellular autophagy. (18th January 2022) - Needs, Sarah H.; Bootman, Martin D.; Grotzke, Jeff E.; Kramer, Holger B.; Allman, Sarah A.
Abstract : The polycaspase inhibitor Z‐VAD‐fmk acts as an inhibitor of peptide: N ‐glycanase (NGLY1), an endoglycosidase which cleaves N ‐linked glycans from glycoproteins exported from the endoplasmic reticulum (ER) during ER‐associated degradation (ERAD). Both pharmacological N ‐glycanase inhibition by Z‐VAD‐fmk and siRNA‐mediated knockdown (KD) of NGLY1 induce GFP‐LC3‐positive puncta in HEK 293 cells. The activation of ER stress markers or induction of reactive oxygen species (ROS) is not observed under either condition. Moreover, Ca 2+ handling is unaffected when observing release from intracellular stores. Under conditions of pharmacological NGLY1 inhibition or NGLY1 KD, upregulation of autophagosome formation without impairment of autophagic flux is observed. Enrichment of autophagosomes by immunoprecipitation (IP) and mass spectrometry‐based proteomic analysis reveals comparable autophagosomal protein content. Gene ontology analysis of proteins enriched in autophagosome IPs shows overrepresentation of factors involved in protein translation, localization and targeting, RNA degradation and protein complex disassembly. Upregulation of autophagy represents a cellular adaptation to NGLY1 inhibition or KD, and ATG13‐deficient mouse embryonic fibroblasts (MEFs) show reduced viability under these conditions. In contrast, treatment with pan‐caspase inhibitor, Q‐VD‐OPh, does not induce cellular autophagy. Therefore, experiments with Z‐VAD‐fmk are complicated by the effects of NGLY1 inhibition, including induction of autophagy, and Q‐VD‐OPh represents an alternative caspase inhibitor free from this limitation. Enzymes: Peptide: N ‐glycanase1, Peptide‐ N (4)‐( N ‐acetyl‐beta‐glucosaminyl)asparagine amidase [EC:3.5.1.52 ]. Abstract : Inhibition of NGLY1 by polycaspase inhibitor Z‐VAD‐fmk in HEK293 cells leads to induction of autophagy and increase in autophagosome formation rather than disruption of autophagic flux. Similarly, autophagy induction is observed with NGLY1 siRNA knockdown. Immunoprecipitation and proteomic analysis reveal comparable autophagosomal protein content in both Z‐VAD‐fmk treatment and NGLY1 knockdown. The alternative broad‐spectrum caspase inhibitor Q‐VD‐OPh does not inhibit NGLY1, and no induction of autophagy is observed.